1991
DOI: 10.1017/s0018246x00017507
|View full text |Cite
|
Sign up to set email alerts
|

Viscount Scudamore's ‘Laudianism’: the Religious Practices of the First Viscount Scudamore

Abstract: Viscount Scudamore had three great passions: God, cider and cattle, in that order. He was remembered for cultivating cider apples, breeding cattle, his learning, and most of all for his piety, rebuilding one church, endowing others and aiding distressed divines during the interregnum. Many commended his erudition. He stood on the fringes of that republic of letters which revolved around Mersenne, a friend of the philosophers Hobbes, DuBosc and Grotius, and known to Samuel Hartlib who considered him ‘a great sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…82 In the following decade it was this concern over sacrilege that led Viscount Scudamore to rebuild the church of Abbey Dore in Herefordshire and restore impropriated tithes. 83 The sanctity and due reverence for churches was thereby threatened by these enemies of the Temple. Adams concluded that while the 'Anabaptists' would 'take God from the Temple', the sacrilegious would 'take the Temple from God'.…”
Section: IImentioning
confidence: 99%
“…82 In the following decade it was this concern over sacrilege that led Viscount Scudamore to rebuild the church of Abbey Dore in Herefordshire and restore impropriated tithes. 83 The sanctity and due reverence for churches was thereby threatened by these enemies of the Temple. Adams concluded that while the 'Anabaptists' would 'take God from the Temple', the sacrilegious would 'take the Temple from God'.…”
Section: IImentioning
confidence: 99%
“…56 The English dimension to the changes made to St Giles' has been overlooked, and in particular the influence of the remodelled cathedrals south of the border. For while, as in England, there was a resurgence of building work in the early seventeenth century -repairing and constructing new churches 57 -the restoration of St Giles' seems to have been part of a wider agenda, linked with the religious policies of the Crown. One hostile contemporary observer, John Row, commenting on the proposed changes to St Giles', noted that 'antichristian Bishops had a great care of all gorgeous and pompous outwards; but unpreaching prelats was never carefull to fitt kirks for the hearing of the word of God'.…”
mentioning
confidence: 99%